The expression of ghrelin O-acyltransferase (GOAT) in human tissues - Lim, C; Kola, B; Grossman, A; Korbonits, M (2011)
Ghrelin is a circulating growth hormone-releasing and appetite-inducing brain-gut peptide. It needs to be acylated on its serine-3 with octanoate for its endocrine actions. The acyl-transferase that catalyses ghrelin octanoylation has recently been identified and named as GOAT (ghrelin O-acyltransferase); GOAT enzyme is coded by the MBOAT4 gene. This study aimed to investigate GOAT expression in the human. The distribution of GOAT mRNA expression was studied in various human tissues using classical and real-time reverse transcription and polymerase chain reaction. GOAT expression was found in all tissues studied (stomach, adrenal cortex, breast, right and left colon, duodenum, jejunum, ileum, fat, Fallopian tube, gallbladder, lymph node, lymphocyte cell line, kidney, liver, lung, muscle, myocardium, pituitary, oesophagus, pancreas, ovary, placenta, prostate, testis, spleen and thyroid). The widespread expression of GOAT corresponds to the widespread distribution of ghrelin expression. GOAT expression was high in stomach and gut, the major ghrelin-secreting tissues, and in the pituitary, in which ghrelin is known to show autocrine and paracrine effects. Identification of GOAT expression in various tissues support the concept that in addition to the important endocrine effect of acylated ghrelin, the paracrine effects of locally synthetised and acylated ghrelin may be important. © The Japan Endocrine Society.